An Open‐label Phase 1 Dose‐escalation Clinical Trial of a Single Intravenous Administration of Gemcitabine in Dogs with Advanced Solid Tumors. (March 2015) - Marconato, L.; Finotello, R.; Bonfanti, U.; Dacasto, M.; Beatrice, L.; Pizzoni, S.; Leone, V.F.; Balestra, G.; Furlanello, T.; Rohrer Bley, C.; Aresu, L.
Abstract : Background: A broad range of gemcitabine dosages have been used in dogs. Hypothesis/Objectives: To determine maximally tolerated dose (MTD), dose‐limiting toxicity (DLT), and preliminary antitumor activity of intravenous administration of gemcitabine in dogs with advanced solid tumors. Animals: Twenty‐two client‐owned dogs. Methods: Dogs with advanced cancer were prospectively enrolled in an open‐label Phase 1 study of gemcitabine. Gemcitabine was administered as a 30‐minute intravenous bolus starting at 800 mg/m 2, using escalation of 50 mg/m 2 increments with 3 dogs per dose level. MTD was established based on the number of dogs experiencing DLT assessed after 1 cycle. Treatment continued until disease progression or unacceptable toxicosis. Additional dogs were enrolled at MTD to better characterize tolerability, and to assess the extent and duration of gemcitabine excretion. Results: Twenty‐two dogs were treated at 4 dose levels, ranging from 800 to 950 mg/m 2 . Neutropenia was identified as DLT. MTD was 900 mg/m 2 . DLT consisting of grade 4 febrile neutropenia was observed at 950 mg/m 2 in 2 dogs. There were no nonhematologic DLTs. Twenty dogs received multiple doses, and none had evidence of severe toxicosis from any of their subsequent treatments. At 900 mg/m 2, 2 complete and 5 partial responses were observed in dogs with measurable tumors. The amount of gemcitabine excreted in urine decreased over time, and was undetectable after the first 24 hours. Conclusions and Clinical Importance: The recommended dose of gemcitabine for future Phase 2 studies is weekly 900 mg/m 2 . In chemotherapy‐naïve dogs with advanced solid tumor this dose level merits further evaluation.